1979
DOI: 10.1007/bf00499060
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake, ethanol-induced narcosis and intoxication in rats following neonatal 6-hydroxydopamine or 5,7-dihydroxytryptamine treatment

Abstract: Newborn rats were treated with 5,7-dihydroxytryptamine (5,7-HT; 2 x 100 mg/kg s.c., 24 h interval) after pretreatment with desipramine (20 mg/kg s.c.) for depletion of brain 5-hydroxytryptamine (5-HT) or with 6-hydroxydopamine (6-OHDA; 3 x 100 mg/kg s.c., 24 h interval) for selective reduction of brain noradrenaline (NA). The 5,7-HT treatment resulted in a 53% reduction in endogenous 5-HT in the cerebral cortex and a 60% increase in the pons-medulla when determined in adult rats. The 5-HT content in the midbra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However disruptions of DA signaling through lesioning of accumbens DA inputs do not impact voluntary ethanol intake (Rassnick et al 1993). Lesions of ascending NE tracts can generate increases (Kiianmaa and Attila 1979;Kiianmaa et al 1975) or decreases in ethanol intake Corcoran et al 1983).…”
Section: Effects Of Noradrenergic Receptor Modulation On Alcohol-related Behaviors and Neural Systemsmentioning
confidence: 99%
“…However disruptions of DA signaling through lesioning of accumbens DA inputs do not impact voluntary ethanol intake (Rassnick et al 1993). Lesions of ascending NE tracts can generate increases (Kiianmaa and Attila 1979;Kiianmaa et al 1975) or decreases in ethanol intake Corcoran et al 1983).…”
Section: Effects Of Noradrenergic Receptor Modulation On Alcohol-related Behaviors and Neural Systemsmentioning
confidence: 99%
“…Studies have also shown that the anticipation of a reward increases the firing of accumbal dopamine neurons [41]. It should, however, be mentioned that results from studies with lesion of the mesocorticolimbic dopamine pathways have shown contradicting results with both decreased [48][49][50] and unaltered alcohol intake [51][52][53][54][55][56]. These inconsistent results indicate that the role of accumbal dopamine in reinforcement is complex and highlights that the rewarding properties of alcohol may extend beyond direct or indirect effects on dopamine, involving interactions with several other neurotransmitters including acetylcholine, glutamate, GABA, serotonin (5HT), noradrenaline, taurine and opioids, as well as hormones and peptides [24,57,58].…”
Section: Preclinical Evidence: Acute Alcohol Exposure and Dopaminementioning
confidence: 99%
“…Previous studies witl, rats tad skown that neonatal treatment witl tl,e neurotoxin 6-! ydroxydopamine I01 (6-OHDA), which causes lesions of catecholaminergic neurons, produces severe, long-lasting impairments in avoidance learning (Shaywitz et al, 1976 and without affecting early sleep-wake behavior (Adrien, 1981) or adult voluntary alcohol consumption (Kiianmaa and Attila, 1979). Early clomipramine exposure, however, has not been found to affect avoidance learning in rats (Mirmiran et al, 1981).…”
Section: Introductionmentioning
confidence: 99%